Effect of carbohydrate source on productive performance, ruminal and systemic health of grazing cows - Gómez-Osorio, Luis M.; Posada-Ochoa, Sandra L.; Rosero-Noguera, Ricardo; Olivera-Angel, Martha E. (Revista Colombiana de Ciencias Pecuarias, 2020)
Background: The nutritional limitations of Cenchrus clandestinus –i.e., high protein and low energy concentrations- make it necessary to supplement cows with non-fibrous carbohydrate (NFC) sources to improve productive performance. Nevertheless, such supplementation can lead to ruminal acidosis. Objective: To evaluate partial replacement of corn grain (Zea mays, ZM) with sorghum grain (Sorghum vulgare, SV), cassava root (Manihot esculenta, MES) or citrus pulp (Citrus sp., C) on milk yield and quality, ruminal pH and health of grazing cows. Methods: Eight Holstein cows were evaluated in a 4 x 4 Latin square design during the first 60 days of lactation. Treatments (isoenergetic rations, 1.45 ± 0.003 Mcal NEL/kg DM) consisted of a mixture of grass and four concentrates with different NFC sources. Results: No differences in dry matter intake, feed efficiency, ruminal pH, hematological and metabolic profile were observed between treatments. Rumen pH was higher than 6.0, confirming the absence of ruminal acidosis. Milk yield (energy-corrected), protein, and total solids were higher for MES vs. C. Conclusions: None of the NFC sources tested compromised the ruminal or systemic health of the cows, while MES improved milk yield and quality.